Patrābalī - Ray, Satyajit,Ray, Sandip (Bicitrā, 2022)
Collection of letters written by an Indian director, screenwriter, documentary filmmaker and author to one of his associate Ajeẏa Rāẏa, 1935-2008, Bengali children's writer; with fascimile reproduction of the handwritten letters.
Keywords: Briefsammlung; Ray; Satyajit; 1921-1992; Correspondence.; Rāẏa; Ajeẏa; 1935-2008; Correspondence.; Motion pictures; India; West Bengal; History.; Children's literature; Bengali; History and criticism.